Whole-genome sequencing of Sphingobium baderi SC-1 and identification of a crucial 3-phenoxybenzoic acid-degrading gene - Li, Qin; Zhou, Qiao; Chen, Yuan; Hu, Kaidi; Sarrà, Montserrat; Li, Jianlong; Liu, Aiping; Zou, Likou; Liu, Shuliang (Frontiers in Microbiology, 2024)
As an efficient degradation strain, Sphingobium baderi SC-1 can breakdown 3-phenoxybenzoic acid (3-PBA) with high proficiency. To investigate the internal factors that regulate this process, we conducted whole-genome sequencing and successfully identified the pivotal 3-PBA-degrading gene sca (1230 bp). After sca was expressed in engineered bacteria, a remarkable degradation efficiency was observed, as 20 mg/L 3-PBA was almost completely decomposed within 24 hours. The phenol was formed as one of the degradation products. Notably, in addition to their ability to degrade 3-PBA, the resting cells proficiently degraded 4'-HO-3-PBA and 3'-HO-4-PBA. In conclusion, we successfully identified and validated sca as the pivotal enzyme responsible for the efficient degradation of 3-PBA from Sphingomonas baderi, providing a crucial theoretical foundation for further explorations on the degradation potential of SC-1.